1993
DOI: 10.1017/s0043174500057532
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine Reduces Primisulfuron Transport to Meristems of Giant Foxtail (Setaria faberi) and Velvetleaf (Abutilon theophrasti)

Abstract: Greenhouse and laboratory studies were conducted to determine the effect of atrazine on efficacy, absorption, translocation, and metabolism of primisulfuron applied to velvetleaf and giant foxtail. Efficacy of primisulfuron was reduced by 18 and 22% when applied at 20 and 40 g ai ha−1, respectively, in combination with 1.7 kg ai ha−1atrazine to velvetleaf. Efficacy of primisulfuron was reduced by 15 and 16% when applied at 30 or 60 g ai ha−1, respectively, in combination with 1.7 kg ai ha−1atrazine to giant fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…On the basis of reports of efficacy in the literature, it was expected that velvetleaf seedling mortality would be much greater (70 to 100%) than that observed here (Buhler et al 1990;Fielding and Stoller 1990;Hart and Penner 1993;Jordan et al 1997;Krausz et al 1995;Mills and Witt 1989;Niekamp and Johnson 2001). The reason for reduced mortality may be that these experiments were conducted in the absence of competition from the crop.…”
Section: Mortalitymentioning
confidence: 67%
“…On the basis of reports of efficacy in the literature, it was expected that velvetleaf seedling mortality would be much greater (70 to 100%) than that observed here (Buhler et al 1990;Fielding and Stoller 1990;Hart and Penner 1993;Jordan et al 1997;Krausz et al 1995;Mills and Witt 1989;Niekamp and Johnson 2001). The reason for reduced mortality may be that these experiments were conducted in the absence of competition from the crop.…”
Section: Mortalitymentioning
confidence: 67%
“…Fall panicum and giant foxtail control were reduced by 14 and 15 percentage points, respectively, when atrazine plus COC was added to foramsulfuron. Atrazine has been reported to antagonize other sulfonylurea herbicides (Dobbels and Kapusta 1993;Hart and Penner 1993). In fact, Hart and Penner (1993) reported that this antagonism was attributed to reduced translocation of the sulfonylurea herbicide in giant foxtail but there was no effect on absorption or metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Atrazine has been reported to antagonize other sulfonylurea herbicides (Dobbels and Kapusta 1993;Hart and Penner 1993). In fact, Hart and Penner (1993) reported that this antagonism was attributed to reduced translocation of the sulfonylurea herbicide in giant foxtail but there was no effect on absorption or metabolism. However, when MSO was added to the atrazine and foramsulfuron tank mixture, fall panicum control (98%) and giant foxtail control (86%) were not different from the foramsulfuron-alone treatment (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Phloem transport can be slow (Derr et al, 1985;Peregoy et al, 1990; Camacho et al, 1991). Instances where plants transclocate herbicides basipetally through phloem more rapidly may relate to observed patterns of efficacy (Hart and Penner, 1993). Response to fluazifop was dependent on translocation (Derr et al, 1985).…”
Section: Introductionmentioning
confidence: 99%